Genus-level records of mite-host associations on ornamental plants across lowland and highland zones of South Sumatra, Indonesia - CHANDRA IRSAN; FADHILA RAHMI; ERISE ANGGRAINI; SITI HERLINDA; MUHAMMAD UMAR HARUN; AGUS HERMAWAN; AHMAD MUSLIM; DELLANIA EKA RINDIANI; NURLAILI HABIBI DANATA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Irsan C, Rahmi F, Anggraini E, Herlinda S, Harun MU, Hermawan A, Muslim A, Rindiani DE, Danata NH. 2026. Genus-level records of mite-host associations on ornamental plants across lowland and highland zones of South Sumatra, Indonesia. Biodiversitas 27 (4): d270412. https://doi.org/10.13057/biodiv/d270412. Ornamental plants are widely cultivated in Indonesia and can host diverse mite communities, including phytophagous pests and predatory species. However, information on mite diversity and host associations on ornamental plants in South Sumatra remains limited. This study aimed to document mite genera and their host plant associations on ornamental plants in lowland (≤100 m asl) and highland (≥700 m asl) areas of South Sumatra. Field surveys were conducted from August to October 2025 in North Indralaya (lowland) and Pagar Alam (highland). Sampling was purposive and focused on ornamental plants showing visible symptoms associated with mite infestation. Infested plant tissues were collected, and mite specimens were prepared using slide-mounting techniques with Canada balsam for morphological identification under compound microscopes. Identification was conducted to genus level based on diagnostic morphological characters. A total of ten ornamental plant species were recorded in the lowland area and sixteen species in the highland area. Four mite genera belonging to four families were identified: Tetranychus (Tetranychidae) and Brevipalpus (Tenuipalpidae) as phytophagous mites, and Amblyseius (Phytoseiidae) and Bdellodes (Bdellidae) as predatory mites. Phytophagous mites were associated with symptoms such as chlorotic spots, leaf discoloration, and leaf curling, while predatory mites were observed on several host plants where phytophagous mites were present. Because sampling targeted symptomatic plants, the results represent descriptive records of mite occurrence and host associations rather than quantitative comparisons between altitudinal zones. This study provides the first genus-level documentation of mite-host associations on ornamental plants across contrasting altitudinal zones in South Sumatra, contributing baseline data for future studies on mite biodiversity and integrated pest management.